THE CONCEPT OF THE IDEAL TEACHER ACCORDING TO KH. MUHAMMAD HASYIM ASY'ARI - Halid, Ahmad; Faishol, Riza (Program Studi Pendidikan Agama Islam, 2022)
This article reveals the concept of the ideal teacher according to KH. Hasyim Asy'ari. Effective education is that there is an ideal teacher. The ideal teacher is a teacher who understands teacher ethics and educates students conscientiously and meets the standardization of requirements as a teacher, namely having knowledge, faith, noble character and having learning tools and implementing well as well as assessing and improving learning. This article has a problem, namely how the concept of an ideal teacher according to KH. Hasyim Asy'ari. This study uses a qualitative and literary approach by sharpening comparative analysis and triangulation. The result of this research is that the teacher should apply morality as an educator and teacher, the teacher writes the subject matter and the teacher cleans the mind and aims to get the pleasure of Allah swt. A good teacher is a teacher who has morals to students, namely his noble personality when carrying out his functions and roles as teachers; educate, teach and train, both inwardly. Outwardly, such as in speaking softly, spreading greetings, mastering learning materials and methods, easy-to-understand delivery and so on.